Rola terenowej administracji publicznej w przygotowaniu ludności do przetrwania w sytuacjach kryzysowych - Błażewski, Maciej (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The aim of the article is to define the scope of activities of local public administration in preparing the population to survive in crisis situations. The research included an analysis of the provisions concerning the crisis situation, which are expressed in the Act on Crisis Management and the Act on Press Law. The research was conducted using the analytical and dogmatic method. The research has shown that activities of the local authorities cover information and ensure survival of the population. These activities are interrelated and can be distinguished as direct and indirect. Every person can take action in order to survive in the time of the crisis situation, taking into account the activities of the local authorities.
Keywords: terenowa administracja publiczna; sytuacje kryzysowe; potrzeby ludności; działania administracji publicznej; zasada pomocniczości; płaszczyzny działań organów administracji publicznej